What is democratic evaluation? - Picciotto, R. (2013)
This article from Robert Picciotto provides an overview of democratic evaluation, particularly with reference to its use in the European Uni on context. "Can evaluation strengthen the democratic process? Specifi cally can it help fill the democratic deficit (limited transparency; w eak bureaucratic accountability, etc.) often ascribed to the European Union? First and foremost, evaluators operating in the European space should be committed to the ethical and democratic values of the Europe an project and the promotion of its social inclusion and cohesion idea ls. But two other sets of challenges must also be met: those that rela te to evaluation in democracy and those that relate to democracy in ev aluation. The former has to do with the macro positioning of evaluatio n processes in society. The latter has to do with the evaluation appro aches and methods used in deliberative democratic decision making proc esses." (Picciotto, 2013)